English writing instruction in Norwegian upper secondary schools – a linguistic and genre-pedagogical perspective - Horverak, May Olaug (My University, 2016)
This thesis investigates 1) How is English writing instruction carried out in upper secondary schools in Norway, and 2) What effects does applying systemic functional linguistics through a genre-pedagogy approach to teaching writing have on students’ writing skills? It is an article-based thesis comprising four articles and an extended abstract. The general theoretical framing of this thesis is systemic functional linguistics (SFL) and genre-pedagogy, an approach to teaching writing developed in Australia based on Halliday’s SFL. The first three articles investigate the first research question, how writing instruction is carried out from both a teacher and student perspective. Teachers were interviewed and observed, and students were surveyed. The findings showed that practices vary, but there seems to be an emphasis on teaching how to structure argumentative writing and focusing on adjusting language to context. In addition, some teachers use formative assessment strategies integrated in their writing instruction. These findings reveal a type of practice in line with a genre-pedagogical approach. The fourth article answers the second research question, what effects applying SFL through genre-pedagogy has on students writing skills. A quasi-experiment was carried out, which included a teaching intervention focused on how to write argumentative texts. The main finding was that the students improved significantly from pre to post-test regardless of gender, first language and level.
Wydział Anglistyki UAM / Faculty of Humanities and Education University of Agder, Krisitansand, Norway
Keywords: systemic functional linguistics; genre-pedagogy; English writing instruction; feedback practices